Nanoparticles in thermotropic and lyotropic liquid crystals - Chen, Chung-Hao; Dierking, Ingo (Frontiers in Soft Matter, 2025)
Over the last few decades many applications of liquid crystals have been developed, including the widely employed technology of low-power, flat-panel liquid crystal displays (LCDs), but also sensors, photonic devices and other non-display applications employed in medicine and drug delivery. In recent years, the research trends have shifted in other directions. Nanotechnology and nanoscience have garnered significant attention in liquid crystal research since various nanomaterials or nanoparticles (NPs) can be added directly to the liquid crystalline mesogenic phases. The main idea is to modify the physical properties of liquid crystals or to increase their functionality through the addition of nanomaterials, but also to exploit the self-assembly and spontaneous ordering of LCs into structures or patterns that can be templated by dispersed particles. The neat liquid crystals and the doped nanoparticles/nanomaterials exhibit different behaviours when mixed together. The nanoparticles can influence the alignment and orientation of liquid crystals, and their interaction with the liquid crystals causes the changes in the optical, electrical, and mechanical characteristics of the composite. At the same time the liquid crystal can affect the ordering, structuring and properties of the nanomaterials, for example by transfer of helical order. In this review, we discuss the effects of nanoparticles dispersed in liquid crystals. Several categories of nanomaterials such as metallic, carbon allotropes, nanorod and nanowires will be introduced, together with particles of additional functionality, like ferroelectricity, semiconductors and quantum dots. The combination of liquid crystals and nanoparticles leads to a wide range of applications and novel technologies.